Diversifying into the branches: Species boundaries in African green and bush snakes, Philothamnus (Serpentes: Colubridae) - Engelbrecht, Hanlie M.; Branch, William R.; Greenbaum, Eli; Alexander, Graham J.; Jackson, Kate; Burger, Marius; Conradie, Werner; Kusamba, Chifundera; Zassi-Boulou, Ange-Ghislain; Tolley, Krystal A. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •The colubrid Green and Bush Snakes of the genus Philothamnus are monophyletic.•Improved genetic and geographical sampling (14 of the 21 nominal taxa).•Up to seven candidate species were identified.•Philothamnus natalensis occidentalis is raised to a full species. The African green and bush snakes of the genus Philothamnus currently comprises 21 species and three subspecies and occurs throughout sub-Saharan Africa. The genus has been the subject of previous taxonomic revisions based on traditional morphological characters and limited genetic assessment, and may not reflect their evolutionary history. Indeed, previous findings based on phylogenetics show discordant results of interspecific relationships and question the monophyly of the genus, although taxon sampling has been limited to date. We investigated phylogenetic affinities within Philothamnus with more inclusive genetic and geographical sampling, with the aim of better understanding their evolutionary history, so that future taxonomic revision of Philothamnus can be better informed. Species relationships were examined within a phylogenetic context and sampling included 133 ingroup samples from 16 taxa. Phylogenies were constructed in Bayesian and likelihood frameworks using three mitochondrial (16S, cyt b and ND4) and two nuclear (c-mos and RAG1) markers. Competing hypotheses relating to the monophyly of the genus were tested with a Shimodaira-Hasegawa test. To examine species boundaries, Bayesian General Mixed Yule-Coalescent Model and multi-rate Poisson Tree Processes analyses were conducted. In addition, a barcoding approach was used to further clarify species-level relationships by comparing frequency distributions between intra- and interspecific sequence divergence. The genus was recovered as monophyletic; however, species-delimitation results suggest that the current taxonomy does not reflect the evolutionary history of this group. For example, Philothamnus s. semivariegatus is paraphyletic, with at least four distinct clades. Philothamnus carinatus consists of two cryptic (sister) lineages from Central and West Africa that are deeply divergent, suggesting a long history of isolation between those regions. Furthermore, the subspecies P. n. natalensis and P. n. occidentalis show strong support for species-level divergence, which reflects their morphological and ecological differences. Accordingly, we elevate P. occidentalisnov. comb. to a full species. A fully informed taxonomic revision of these taxa will require additional morphological and ecological data for corroboration, but it seems that the morphological characters (e.g. scalation, dentition) used to describe these species to date are labile within and between species. This most likely has clouded our understanding of the species boundaries within the genus. Our phylogeny and species-delimitation analyses should provide a sounder framework for taxonomy, but may also prove useful toward understanding the morphological adaptations of these species to their respective habitats.